Konspiracja młodzieżowa na ziemiach polskich w latach 1944–1956 - Wołoszyn, Jacek (Pamięć i Sprawiedliwość, 2011)
Between 1944 and 1956 those of young people who expressed their opposition to the communist ideology and atheism present in everyday life and also to the permanent violation of freedom, made a decision to get involved in underground activity. According to the IPN’s records, they formed throughout the country at least 972 clandestine organizations with 11 thousand members. Newly created associations referred to various traditions (scouting movement, religion, Home Army, WiN [Wolność i Niezawisłość, Freedom and Independence], BCh [Bataliony Chłopskie, Polish Peasants’ Battalions], NSZ [Narodowe Siły Zbrojne, National Armed Forces], peasant and national movements). In the youth’s conspiracy work three phases could be distinguished. The first one was a present activity of that time – preparation to the change of political system mainly due to an armed struggle. Young people gained military qualifications and conducted campaign aimed at educating conspiracy members about the ongoing political situation and at formation of the civil attitude of the local communities (in leaflets – rather than in the underground press – they appealed to people to preserve their national identity, to maintain resistance and to remain independent of official propaganda’s influence). The next planned phase was to be an direct involvement in military struggle against the enemy, at the side of Polish Army advancing form the West, leading to a restoration of the independence of the country. There were however two major categories of associations – military and scout. Józef Piłsudski was chosen the ideological patron of some of them, whereas others referred to the national conceptions or even to the theory of socialism simultaneously rejecting its contemporary concept. They youth conspiracy activists had vision of the Poland’s future. It was to become democratic country, guaranteeing political and economic freedom and civil liberties. Regardless of the fact that during the first decade of Peoples’ Republic of Poland the youth conspiracy members were not numerous, they were those who – after the defeat of “adult underground” – took over an heritage of an anticommunist resistance: gros grup (about 66 per cent) was active between the years 1949 and 1953.